Increased serum levels of interleukin-8 in patients with tension-type headache. (August 2015) - Domingues, Renan B; Duarte, Halina; Rocha, Natália P; Teixeira, Antonio L
Background and objectives: The pathophysiology of tension-type headache is not well understood. Increased peripheral levels of pro-inflammatory cytokines may act as mediators of several chronic pain disorders. The aim of the present study was to investigate the peripheral levels of chemokines in patients with tension-type headache. Methods: This was a cross sectional study evaluating serum levels of chemokines in age and sex-matched tension-type headache patients, ictally and interictally, and control participants. Beck Depression and Anxiety Inventories were recorded. Serum levels of monocyte chemoattractant protein-1, macrophage inflammatory protein 1α, regulated on activation, normal T cell expressed and secreted, eotaxin, eotaxin-2, interleukin-8, interferon gamma induced protein-10 were measured by enzyme-linked immunosorbent assay. Results: A total of 96 participants (48 tension-type headache, 48 controls) were included. Interleukin-8 levels were significantly increased in patients with tension-type headache when compared to controls (413.8 (123.4–1756.3) and 329 (107.8–955.6), respectively, P  = 0.025). Anxiety and depression scores were higher in patients with tension-type headache but interleukin-8 increase in tension-type headache patients persisted after controlling for anxiety and depression symptoms. Patients with headache at the time of assessment had increased monocyte chemoattractant protein-1 levels when compared with patients without headache (2809.3 (1101–6122.2) and 1630.2 (669.3–31056.8), respectively P  = 0.026). Patients with episodic and chronic tension-type headache had no significant differences in serum chemokines levels. Conclusion: Interleukin-8 was increased in tension-type headache and monocyte chemoattractant protein-1 was higher in tension-type headache patients with headache, suggesting that pro-inflammatory mechanisms may participate in tension-type headache pathophysiology.